Beyond smartphones: How citizen volunteers are supporting the drylands livestock market intelligence platform KAZNET in Kenya - Onyango, Polycarp; Shikuku, Kelvin Mashisia (International Livestock Research Institute, 2024)
In the drylands of Kenya, the digital transformation of livestock markets is gathering pace, and contributing to that is a platform named KAZNET, developed by the International Livestock Research Institute (ILRI) with support from USAID and FCDO, and scaled through Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) project and the CGIAR Research Initiative on Livestock and Climate. KAZNET provides demand driven market intelligence for livestock keepers in arid and semi-arid lands (ASALs) of Kenya and Ethiopia. This platform is now integrated into the Government-led Kenya Agricultural Observatory Platform (KAOP) managed by the Kenya Agricultural Livestock Organization KALRO to enhance the delivery of real-time livestock market data, supplementing the Kenya Integrated Agricultural Management Information System (KIAMIS). At the core of KAZNET success is the involvement of about 52 citizen volunteers, aptly named ‘contributors,’ spread across Kenya’s dryland counties. These contributors are responsible for inputting key data into the platform and disseminating that information to local communities.